EVALUASI KEBIJAKAN MUSYAWARAH RENCANA PEMBANGUNAN (MUSRENBANG) DITINGKAT KECAMATAN DALAM MENINGKATKAN PEMBANGUNAN: Studi Kasus Pada Kecamatan Junrejo Kota Batu Provinsi Jawa Timur - Hadiwiyono Wiyono; Abner Ayah Doku Bani (STIA MALANG, 2023)
Evaluation is one of the important stages that must be carried out in any public policy process,musrenbang evaluation aims to find out how far the success of development is achieved. Musrenbang is short fordeliberation of development plans. The meaning of musrenbang is a forum between actors in order to compilenational development plans and regional development plans. Implementation is regulated in law No. 25 of 2004concerning the National development planning system. The purpose of this study is to find out the policy modelfor deliberation of development plans (musrenbang) at the sub-district level in improving development in junrejosub-district, as well as to find out who is responsible for evaluating the deliberative policy of development plans(musrenbang) at the sub-district level in improving development in junrejo sub-district. The types of researchused in research are qualitative research methods, data collection techniques through three methods, namelyinterviews, documentation, and observation. The informant determination technique is to use purposive sampling.Meanwhile, to test the validity of the data, it is to use data triangulation techniques. The results of this study showthat the mechanism for evaluating the deliberation of development plans that apply in musrenbang in Junrejosub-district is to recapitulate the data on development goals submitted by each village and / or kelurahan, theformation of a list of priority activities for the preparation of village development work plans for the plannedfiscal year, the formation of a priority list of regional problems in the village to be delivered in the sub-districtmusrenbang, the formation of a list of team names, village delegates, who will follow the sub-district musrenbang,the last is the formation of the village musrenbang minutes.